Examining the validity and reliability of the academic entitlement scale in Turkish culture - Serel Akdur Çiçek; Aysegul Bakır; Büşra Aslan Cevheroğlu; Adem Kantar (International Journal of Assessment Tools in Education)
This study aims to adapt the Academic Entitlement Scale to Turkish culture and examine the scale's measurement invariance according to gender. The study was conducted with 372 university students aged 18 and 54 (I = 20.90). The study used the Academic Entitlement Scale, Rosenberg Self-Esteem Scale, Narcissistic Personality Inventory, and Locus of Control Scale as data collection tools. Confirmatory factor analysis was performed to identify the construct validity of the scale. The measurement invariance of the scale according to gender was examined using multi-group confirmatory factor analysis. Correlations between research variables were analyzed with the Pearson Correlation Test. Cronbach's Alpha was performed to measure the internal consistency reliability of the study. As a result of the analyses, it was determined that academic entitlement was positively correlated with self-esteem and external locus of control. In addition, it was revealed that the externalized responsibility sub-dimension was positively correlated to narcissism. The research findings indicate that the scale is a valid and reliable measurement tool within Turkish culture.